Determine Process Training Key Factors and Job Performance in Higher Education Sector - M. Sharif, Z.; F. Obaid, T.; M. Eneizan, B.; S.S. Abumandil, M. (International Journal of Engineering and Technology, 2018)
The study was proposed to determine key factors in process training and job performance in higher education sector. These has been a sufficient number of studies suggesting that knowledge sharing, transfer climate and motivation to share knowledge facilitate employee training transfer and might increase job performance. There researches about the process training are still inconclusive in the Palestinian context as there is ambiguity that process-training factors such as knowledge sharing, transfer climate and motivation to share knowledge are associated with training transfer and job performance. Hence the current research aimed to examine how process training factors are related to job performance and to investigate the mediating role of training transfer in this relationship. Being quantitative in nature and having a target population of 7651 academic staffs a random sample of 300 comprises of academic staff from different Palestinian higher education institutes. The result suggested that the relationship of transfer climate and job performance is significantly mediated by training transfer. The study provides the discussion and recommendations too.Â Â